Pengaruh Cemaran Logam Berat Kadmium (CD) Terhadap Bentuk Sediaan Jahe Emprit (Zingiber Officinale Var. Amarum) - Devi Oktavia; Maria Mita Susanti (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2023)
The high productivity of ginger in Indonesia ranks fifth out of the ten largest ginger producing countries in the world, for example emprit ginger (Zingiber officinale var. Amarum). Emprit ginger is usually processed into dosage forms such as powder and extract which are widely used as a spicy and off-flavor enhancer in drinks, food or traditional medicine. The growth of emprit ginger plants can be influenced by heavy metal contamination which has toxic effects and is easily absorbed, such as Cadmium (Cd), so that heavy metal Cd contamination needs to be considered as a quality requirement in the manufacture of traditional medicines and processed foods. This study aims to determine the levels and differences in heavy metal Cd contamination in the dosage form of emprit ginger using the Atomic Absorption Spectrophotometry (AAS) method. The type of research used is experimental research. The independent variable of this research is the dosage form of emprit ginger and the dependent variable is Cd metal content. The data obtained were then tested using the Independent Sample T-Test. The results of cadmium (Cd) metal contamination levels in the powder dosage form were an average of - 0.2183 mg/kg and thick extracts with an average of - 0.2225 mg/kg. The results of statistical tests using the Independent Sample T-Test showed that there was no influence of heavy metal Cd contamination on the dosage form of emprit ginger (p>0.05).